The preliminary development and validation of a trauma-related safety-seeking-seeking behaviour measure for youth: the Child Safety Behaviour Scale (CSBS) - Alberici, A; Claxton, J; Meiser-Stedman, R; Smith, P; Ehlers, A; Dixon, C; McKinnon, A (Wiley, 2018)
Safety‐seeking behaviors (SSBs) may be employed after exposure to a traumatic event in an effort to prevent a feared outcome. Cognitive models of posttraumatic stress disorder propose SSBs contribute to maintaining this disorder by preventing disconfirmation of maladaptive beliefs and preserving a sense of current threat. Recent research has found that SSBs impact children's posttraumatic stress symptoms (PTSS) and recovery. In this paper, we sought to develop and validate a novel 22‐item Child Safety Behavior Scale (CSBS) in a school‐based sample of 391 pupils (age 12–15 years) who completed a battery of questionnaires as well as 68 youths (age 8–17 years) who were recently exposed to a trauma. Of the sample, 93.1% (N = 426) completed the new questionnaire. The sample was split (n = 213), and we utilized principal components analysis alongside parallel analysis, which revealed that 13 items loaded well onto a two‐factor structure. This structure was superior to a one‐factor model and overall demonstrated a moderately good model of fit across indices, based upon a confirmatory factory analysis with the other half of the sample. The CSBS showed excellent internal consistency, r = .90; good test–retest reliability, r = .64; and good discriminant validity and specificity. In a multiple linear regression, SSBs, negative appraisals, and number of trauma types each accounted for unique variance in a model of PTSS. This study provides initial support for the use of the CSBS in trauma‐exposed youth as a valuable tool for further research, clinical assessment, and targeted intervention.